Investigating the role of origami algorithm in facades of high-rise buildings to reduce visual pollution and improve urban landscape quality - Tabbasom Tabasi; Amir Farajolahi Rod; Vahid Ahmadi; Hamid Reza Shoaei (Anthropogenic Pollution)
The present study was conducted to identify and prioritize origami components affecting facades of high-rise buildings to explain the role of origami algorithm in improving urban landscape quality and reducing visual pollution. The research had an exploratory nature, and used the method of descriptive-survey data analysis. The research design was carried out in three steps, documentary analysis, Delphi survey and semiotic analysis. A panel of experts (n = 15) was considered as specialists in urban planning, architecture and urban design. Data were analyzed by statistical tests, SPSS-22 software and MAXQDA 2020 software. A hypothetical model of high-rise building made in RHINO software using Grasshopper plugin was applied for simulation. The results of the questionnaires revealed the effects of 18 components on the facade of high-rise buildings and also 12 components on the improvement of urban landscape quality. The findings indicated a correlation between overall dimensions of origami algorithm and urban landscape quality, and showed that the components of ârepetitionâ, âdetailsâ, âgeometryâ and ârhythmâ were most related to the origami algorithm, thereby highlighting the strong impact of the origami algorithm on improving urban landscape quality. According to the simulation results, among the components affecting urban landscape quality, âView compositionâ had the largest contribution with the correlation coefficient of 130, followed by âColorâ and âBalance and symmetryâ with the coefficients of 120. The end of this classification included the component âposition of openingsâ with the coefficient of 2.